2021
DOI: 10.1371/journal.pone.0247548
|View full text |Cite
|
Sign up to set email alerts
|

Use of angiotensin converting enzyme inhibitors and angiotensin receptor blockers associated with lower risk of COVID-19 in household contacts

Abstract: Background Use of angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) has been hypothesized to affect COVID-19 risk. Objective To examine the association between use of ACEI/ARB and household transmission of COVID-19. Methods We conducted a modified cohort study of household contacts of patients who tested positive for COVID-19 between March 4 and May 17, 2020 in a large Northeast US health system. Household members were identified by geocoding and full address matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…Some studies have shown a significant association between ACEi or ARB use and risk of SARS-CoV-2 infection and severity of health outcomes. (14, 15) In contrast to that, our study did not find any association, positive or negative, between ACEi or ARB use and serostatus. This suggests that use of ACEi or ARB may not affect vaccine efficacy, even if their use has the potential to influence risk of disease or its severity.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown a significant association between ACEi or ARB use and risk of SARS-CoV-2 infection and severity of health outcomes. (14, 15) In contrast to that, our study did not find any association, positive or negative, between ACEi or ARB use and serostatus. This suggests that use of ACEi or ARB may not affect vaccine efficacy, even if their use has the potential to influence risk of disease or its severity.…”
Section: Discussioncontrasting
confidence: 99%
“…The systematic search identified 169 observational studies that assessed the associations between RAAS inhibitor use and the risk of contracting a SARS‐CoV‐2 infection and/or experiencing severe COVID‐19 outcomes (Figure 1 ). 8 , 19 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , …”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the Probability of COVID-19 diagnosis was slightly higher among ACEI/ARB users. However, ACEI/ARB users were older and when the cohort was adjusted for age, gender, race/ethnicity, English proficiency, comorbid conditions, time period, including patients with documented hypertension, diabetes, or cardiovascular disease, as well as when including other medications in the models, use of ACEI/ARBs remained associated with a decreased risk of COVID-19 infection in propensity score analyses with a predicted probability of COVID infection 18.6% in ACEI/ARB users vs. 24.5% in non-users, p = 0.03 [8].…”
Section: Resultsmentioning
confidence: 99%
“…This theoretically should increase the risk of covid-19 transmission [16,19,24,30]. But some studies have shown that the use of ACE inhibitors and ARBs has soon reduced the risk of COVID-19 transmission and being symptomatically infected [8,21].…”
Section: Introductionmentioning
confidence: 99%